2018
DOI: 10.1016/j.kjms.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node ratio as an alternative to pN staging for predicting prognosis after neoadjuvant chemotherapy in breast cancer

Abstract: Axillary nodal status is one of the most important prognostic factors in breast cancer. The lymph node ratio (LNR) has been suggested as an independent prognostic factor because the number of dissected and involved lymph nodes might differ across institutions. Neoadjuvant chemotherapy (NAC) has been the preferred treatment method for reducing tumor mass in the breast and axillary area. However, NAC can reduce total number of excised lymph nodes compared with upfront surgery. Therefore, an emerging question is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…Studies in breast cancer patients have shown that LNR can be an independent prognostic factor for DFS and OS, in contrast to residual lymph node status according to ypN grading. 14,15 In the TNBC population, two studies identified better 5-year OS and DFS outcomes with the LNR as opposed to the yPN. 16,17 Previous research showed that the LNR is a good predictor of survival after NAC in nonspecific breast cancer; however, there is lack of information in patients with TNBC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in breast cancer patients have shown that LNR can be an independent prognostic factor for DFS and OS, in contrast to residual lymph node status according to ypN grading. 14,15 In the TNBC population, two studies identified better 5-year OS and DFS outcomes with the LNR as opposed to the yPN. 16,17 Previous research showed that the LNR is a good predictor of survival after NAC in nonspecific breast cancer; however, there is lack of information in patients with TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…One of these parameters, the lymph node ratio (LNR), is defined as the ratio between positive nodes and resected nodes and has shown to be a promising predictor for the prognosis of survival after NAC. Studies in breast cancer patients have shown that LNR can be an independent prognostic factor for DFS and OS, in contrast to residual lymph node status according to ypN grading 14,15 . In the TNBC population, two studies identified better 5‐year OS and DFS outcomes with the LNR as opposed to the yPN 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Any postoperative complications had been documented [e.g., seroma formation, wound infection and time to remove drain]. Surgical techniques had been performed as described by Chen et al [7] The collected data had been coded, fed to personal computer and statistically analyzed using a computer statistical package [ On the other side, table [2] presented the pre-and post-surgery factors that insignificantly associated with positive nodal status in 40 patients. These factors include estrogen receptor, progesterone receptor, tumor grade, and family history…”
Section: Methodsmentioning
confidence: 99%
“…Life expectancy had been also increased to reach 76 years in female and 70 years in males [1] . Nodal status is the most important prognostic factor for survival in BC patients [2] . Before the mid-1990s, axillary dissection was the standard method of staging of locoregional metastatic node, including patients with early BC.…”
Section: Introductionmentioning
confidence: 99%
“…Although lymph node involvement is a common condition in most patients undergoing surgery (14,18), an increase in the number of metastatic lymph nodes can be a sign of poor survival (17). Ultimately, LNR evaluation has been suggested for predicting postoperative survival rate (19)(20)(21)(22)(23). There is no certainty about the value of this ratio and conflicting results have been reported (15,17).…”
Section: Objectivesmentioning
confidence: 99%